Outpatient follow-up or active clinical observation in patients with nonspecific abdominal pain in the emergency department. A randomized clinical trial - (:unkn) unknown (My University, 2008)
Aim. The aim of this study was to determine whether it is safe and cost-effective to discharge nonspecific abdominal pain (NSAP) patients from the Emergency Department (ED) and reevaluate diagnosis later. Methods. Patients aged between 18 and 65 years were enrolled into the study. They had been admitted to the ED for acute abdominal pain with an indefinitive diagnosis after clinical examination and base-line investigations. The patients were randomly assigned into two groups: 1) active clinical observation (ACO), comprising those admitted to the ED observation room; 2) outpatient group (OG), comprising those discharged and asked to return for re-evaluation at 8-12 hours intervals over the following three days. Each patient was examined by an ED physician and a consultant general surgeon. Demographics, blood tests, morbidity and mortality, number of operations, together with 6-month follow-up results were noted. Finally, a patient satisfaction questionnaire 'was administered. Results. A total of 105 patients were enrolled into the study; 50 were randomized to the ACO group and 55 to the OG. There were no statistically significant differences in demographics and blood parameters between the two groups. Overall agreement of ED diagnosis with final diagnosis was 91.4%. Total morbidity was 10% in the ACO group and 7.2% in the OG. There were no statistically differences in morbidities and usage of diagnostic imaging modalities between the two groups (P>0.05). No deaths occurred in either group during the study period. The patients in the ACO group were more keen on returning for re-evaluation and willing to recommend our hospital services to other people (P<0.05). Conclusion. Outpatient evaluation of patients with an ED diagnosis of NSAP may be an option, seems to be safe, is not accompanied by an increased incidence of complications and is efficient if patients are selected properly.
Keywords: Abdominal pain; Emergency service, Hospital.; Follow-up, studies; Monitoring, ambulatory; Observation